2006
DOI: 10.3892/or.16.2.405
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on the recurrence/metastasis of stage II/III colorectal cancer and gastric cancer associated with occult neoplastic cells in lymph node sinuses: Three-year interim results

Abstract: This study was designed to prospectively examine whether the presence of occult neoplastic cells (ONCs) in lymph nodes or positive high-risk (HR) criteria were related to the survival of patients with stage II/III colorectal cancer or gastric cancer. The 3-year relapse-free survival (3Y-RFS) rate was calculated for 79 patients who were registered during a 2-year period. The 3Y-RFS rate was 80.5% in patients without ONCs (n=54) and 84.3% in patients with ONCs (n=25; p=0.9089). Among patients who had stage II/II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Various studies have shown that the detection of intranodal ONCs in LNs indicates the systemic spread of cancer cells more accurately than the ly and v status of the primary tumor (10)(11)(12)(13)(14)(15)(16). In fact, many clusters of extranodal ONCs were observed in the dissected perinodal fat of the present patient, despite the tumor being ly0 and v0.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Various studies have shown that the detection of intranodal ONCs in LNs indicates the systemic spread of cancer cells more accurately than the ly and v status of the primary tumor (10)(11)(12)(13)(14)(15)(16). In fact, many clusters of extranodal ONCs were observed in the dissected perinodal fat of the present patient, despite the tumor being ly0 and v0.…”
Section: Discussionmentioning
confidence: 57%
“…Possible risk factors for the postoperative local recurrence of low rectal cancer including stage I disease are: i) an inadequate resection margin of <2 cm, ii) seeding of tumor cells by large bowel perforation due to operative manipulation or inadequate suturing, iii) implantation of viable tumor cells in the alimentary tract by mechanical anastomosis, and iv) occult microscopic tumor invasion, including visually undetectable microscopic lymph node metastasis and microscopic deposits in the pelvic fat (7)(8)(9). Many studies have also shown a close relationship between the detection of cytokeratin-positive occult neoplastic cells (ONCs) in lymph node sinuses (intranodal ONCs) far from the primary tumor and distant metastasis/recurrence of n0 disease (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Solitary free ONCs in LN sinuses distant from the primary tumor can be detected by cytokeratin immunostaining, but ONCs are also defined as including clusters of ≤10 cells, while malignant microaggregates contain >10 cells (10). ONC clusters have the potential to cause tumor metastasis/ recurrence in any organ, and should be differentiated from micrometastases (0.2-2 mm) anchored in LNs or from ITCs (≤0.2 mm), since ONC clusters seem to be have a higher malignant potential (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…ONCs are also defined as including small clusters of ≤10 cells, while malignant micro-aggregates contain >10 cells 2,3,10) . ONC clusters can theoretically cause recurrence/metastasis in any organ, and should be differentiated from micrometastases (0.2 mm to 2 mm in diameter) anchored in LNs or from ITCs, since ONCs seem to be occult systemic metastases with a higher malignant potential [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%